Announcement Effect of Cross Border M&A on Indian Acquiring Firms - Nagar, Pranav (2008)
Whenever there is an announcement about a merger, especially a cross-border merger, there is an excitement and expectation among the shareholders of the acquiring company. This expectation may or may not convert into an abnormal return. My dissertation identifies this abnormal return and attempts to verify the significance of the same in the short-term. Whether the abnormal returns are significant to the announcement of the merger, determines the success of the merger in the short-term. Though there are many variables involved in determining the overall success of any merger, the immediate market reaction is sufficient to establish a criterion for success.